Evaluation of microstructural and mechanical characteristics of stir cast A356/(0 to 20) wt.% SiCp composites. Issue 1 (March 2021) - Jibin Bose, T C; Hashim, M; Rajeev, V R
Abstract: In this work A356/(0-20%) wt.% SiCp composites were prepared from A356 base alloy through the most economical casting route i.e., stir casting method. Silicon carbide of particle size 23 micron was used as reinforcement to prepare A356/10wt.%SiCp and A356/20 wt.% SiCp composites. Microstructure of A356 and A356/(0-20)wt.% SiCp composites were examined using Leica optical microscope. Microstructural Examination showed that A356/(0-20)wt.% SiCp composites have uniform distribution of SiC particles within the two composites apart from α aluminium and eutectic Si compared to its base alloy. Hardness and tensile test were conducted for heat treated and as cast specimens. It was found that heat treated A 356 alloy and its composites have better hardness than as cast. Tensile tests were conducted on both alloy and its composites and found that brittle fracture was more likely to occur in composites wherein ductile fracture pre dominates in base alloy. XRD analysis of both alloy and its composites showed the major hardening phases such as Al2 Cu, Mg2 Si etc.